Transfusion burden following reduced intensity allogeneic hematopoietic cell transplantation: Impact of donor type. Issue 7 (26th April 2021) - Subramanian, Sitalakshmi; Cohn, Claudia; DeFor, Todd; Welbig, Julie; Brunstein, Claudio; El Jurdi, Najla; Weisdorf, Daniel
Abstract: Background: Transfusions are essential for allogeneic hematopoietic cell transplant (HCT), yet they are influenced by graft, donor, and other factors. Study design: We analyzed transfusions in 165 adult reduced intensity HCTs (2016–2019): HLA matched sibling donor (MSD) (n = 59), matched URD (n = 25), UCB (n = 33), and haploidentical (haplo, n = 48) detailing the cumulative incidence of platelet and RBC transfusion independence, total transfusions (day−10 to day+100) plus transfusion densities (per week) over 110 days. Results: Platelet recovery to 20 × 10 9 /L by 6 months occurred in 39/48 (81.25%) haplo recipients (median 33 [range, 0–139]) days vs. 58/59 (98.3%) MSD (median 10 [0–37]), 21/25 (84%) matched URD (median 20 [0–153]), and 29/33 (87.87%) UCB (median 48 [29–166]) days, p  < .01. Regression analysis demonstrated a lower likelihood of prompt platelet recovery in matched URD, UCB, or haplo HCTs vs. MSD. Recovery to platelet independence was quickest in MSD (median 8 days [range 0–94]), vs. URD (median 16 days [0–99]), UCB (median 57 [0–94]), or haplo (median 45 [12–97]) days, p  < .01. Platelet needs were unaffected by age, conditioning, or acute GVHD. RBC transfusion independence was achieved in 78% of MSD, 64% URD, and 82% UCB, though less frequent (58%) and slowest in haplo recipients, p  < .01. All haplo and UCB recipients required platelet transfusions vs. only 51% of MSD and 76% of URD. RBC needs were highest in UCB and haplo HCTs. Discussion: The transplant donor influences the transfusion burden with greater platelet and RBC needs in haplo and UCB HCT which directly contributes to increased cost of care.